KONSEP ADIL DALAM PERKAWINAN POLIGAMI MENURUT HAKIM PEREMPUAN DALAM PUTUSAN DI PENGADILAN AGAMA - Indah Lestari (Jurnal Justitia Jurnal Ilmu Hukum Dan Humaniora Fakultas Hukum Universitas Muhammadiyah Tapanuli Selatan, 2020)
This article aims to analyze the concept of fairness in polygamous marriage according to female judges at the Depok and East Jakarta Religious Courts. This study is important to do to find out the legal arguments of women judges in their decisions in the Religious Courts. This study is a normative juridical study accompanied by interviews and descriptive qualitative analysis. This article shows that justice in the context of polygamy consists of two, namely fairness in the distribution of physical and mental livelihoods. Fairness in the distribution of living expenses is the ability to provide for the welfare of the wives and children. Meanwhile, the inner support is the applicant's ability to fulfill his inner needs in the form of affection for his wife and children. To guarantee the rights of wives and children, female judges at the religious court determined that there was joint property between the applicant and the respondent. Thus, the joint property of the first wife will not be mixed and potential claims from the prospective wife of the applicant are closed. Likewise, the assets of the children cannot be contested by the children of the applicant's wife.